Analysis of PSM after implementation of CbCR policy in Indonesia - Adang Hendrawan; Ifti Khori Royhan; Arfah Habib Saragih; Milla Sepliana Setyowati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
The Country-by-Country Reporting (CbCR) policy requires that multinational enterprises report financial information of all of their business group members globally. The presence of the information within such policy framework should be reviewed as to whether it will be useful for the Profit Split Method (PSM) implementation. This research used a qualitative approach with data collection techniques including indepth interview. The results indicate that in the future, the PSM will grow in urgency with the development of multinational enterprises and the Anti-BEPS (Base Erosion and Profit Shifting) project. However, the PSM implementation in Indonesia at the present time is still rare due to particular difficulties encountered by both taxpayers and tax authorities. CbCR data alone is not sufficient to be used as a basis for the PSM implementation. Nevertheless, CbCR can still be used by taxpayers as a basis for the PSM implementation in collaboration with other data and information.